IMPROVING THE SYSTEM OF ORGANIZATION AND MANAGEMENT OF PHYSICAL CULTURE AND SPORTS IN THE MODERN ERA - Isakov Erkinjon Tulkinovich (Western European Studies, 2024)
In the modern era, increasing the efficiency of using available resources, optimizing organizational and management structures and introducing innovative technologies is becoming an urgent area for improving the system of organization and management of physical culture and sports. The growing popularity of a healthy lifestyle, interest in active forms of leisure and sporting events determines the need to modernize the mechanisms of state policy in this area, ensuring the availability and quality of physical education, health and sports services. Measures to stimulate the development of mass and professional sports, create conditions for personal self-realization, and increase the competitiveness of Russian sports at the international level are becoming important. Improving the industry management system involves the use of modern approaches to the design, planning and monitoring of physical culture and sports activities, effective interaction between government bodies, business structures and civil society institutions
Keywords: system of organization and management; physical culture and sports; mass and professional sports